Identification of Peptoniphilus harei From Blood Cultures in an Infected Aortic Aneurysm Patient: Case Report and Review Published Literature - Wan, Xue; Wang, Shuang; Wang, Min; Liu, Jinhua; Zhang, Yu (Frontiers in Cellular and Infection Microbiology, 2021)
Gram-positive anaerobic cocci (GPAC) are a commensal part of human flora but are also opportunistic pathogens. We report for the first time a case of Peptoniphilus harei bacteremia in an abdominal aortic aneurysm (AAA) patient. Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) failed to identify the isolate and molecular analysis confirmed it as P. harei. A comprehensive literature review revealed that P. harei is an emergent pathogen. This study serves as a reminder for practicing clinicians to include anaerobic blood cultures as part of their blood culture procedures and especially in situations where there is a high level of suspicion of infection factors in some noninfectious diseases, as mentioned in this publication. Clinical microbiologists should be aware that the pathogenic potential of GPAC can be greatly underestimated leading to incorrect diagnosis on using only method for pathogen identification. Upgradation and correction of the MALDI-TOF MS databases is recommended to provide reliable and rapid identification of GPAC at species level in medical dianostic microbiology laboratories.